Micronutrient intake inadequacies in different types of milk consumers in Indonesian children 1–5 years: dietary modeling with young child milk improved nutrient intakes - Sunardi, Diana; Wibowo, Yulianti; Mak, Tsz Ning; Wang, Dantong (Frontiers in Nutrition, 2023)
Background: Indonesian children under-five have a high prevalence of micronutrient deficiencies. Improving young child feeding practices may be the solution. Increasing the consumption of appropriate milk products could help to reduce nutrient inadequacy. Methods: The objective of this study was to assess nutrient inadequacy in children 1-5 y in Indonesia and to evaluate the potential improvement using dietary modelling analysis. Data from children aged 1-5 years from the Indonesian Individual Dietary Consumption Survey in 2014 were used in this analysis (n=11020). Diet modelling was conducted in two scenarios, substitution volume to volume and calories to calories. Results: The proportion of children consuming young child milk (YCM) was the highest compared to other milk types across all age groups, followed by condensed milk and cow’s milk. YCM, also called “Growing-Up Milk” (GUM), are marketed as a product specifically formulated for the nutritional needs of young children. YCM consumers had lower prevalence of inadequate intakes in iron, zinc, vitamins A, C and D across age groups when compared to condensed milk consumers. The prevalence of inadequate intakes of nutrients in condensed milk consumers was Vitamin A (67%, 64%), folate (92%, 91%), Vitamin D (87%, 84%), iron (84%, 76%), and zinc (76%, 76%) in 1-2y and 3-4y, respectively The substitution of condensed milk with a YCM reduced the prevalence of inadequate intakes of micronutrients, such as Vitamin A, vitamin D, folate, iron and zinc, which are important for immune function. YCM reduced the prevalence of inadequate intakes of micronutrients by 20–40% (Vit A and folate) and 40–50% (Vit D and zinc). The reduction of prevalence of inadequate iron intake was 31% in 1–2y and 63% in 3–4y. Conclusions: The prevalence of inadequate micronutrient intakes was high among children aged 1–5 years old in Indonesia. YCM consumers had better nutrient intake. The substitution of condensed milk with a YCM reduced the prevalence of inadequate of micronutrient intake. Thus, nutrient intakes could be improved by YCM consumption in 1-5 years old children in Indonesia, along with nutrition education on feeding practices. YCM consumption may be the solution for nutrients in adequacy among under five children.